Peran Lingkungan Keluarga dalam Meningkatkan Bahasa Anak Usia Dini di Lingkungan III Pasar Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Khoirunnisah, Khoirunnisah; Khadijah, Khadijah; Nasution, Zulkipli (Darul Yasin Al Sys, 2025)
This study is motivated by the crucial role of the family in developing early childhood language skills, particularly in Lingkungan III Pasar Sibuhuan, Barumun District, Padang Lawas Regency. The research aims to identify family programs that support the enhancement of early childhood language abilities, describe their implementation, and analyze the supporting factors involved in the process. A descriptive qualitative approach was employed, with families and parents as the subjects, and data were analyzed using the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that family programs aimed at supporting children's language development remain suboptimal, primarily due to limited language stimulation, the dominance of regional languages, and restricted access to educational media. The process of language development is significantly influenced by family interaction, peer relationships, and the role of early childhood education institutions. Key supporting factors include active parental involvement, the intensity of social interaction, and institutional support from educational settings. The study concludes that there is a need to raise family awareness and implement further educational programs to optimize early childhood language development within the home environment.